Un altro porno femminista è possibile: aging e lotta agli stereotipi in Dana Vespoli (Altre Modernità, 2020)
Introduzione di Serena GuarracinoUn altro porno femminista è possibile: aging e lotta agli stereotipi in Dana Vespoli di Sofia TorreABSTRACT: After the feminist Porn Wars it is not hard to find specific porn for women, as the female choice section on sites such as Pornhub shows. Dana Vespoli offers a broader definition of what feminist porn can be. She uses sexually explicit imagery to contest and complicate dominant representations of gender, sexuality, race, ethnicity, class, age and body type. She explores concepts of desire, agency, power, beauty, and pleasure against the limits of gender hierarchy and heteronormativity. The main purpose of this paper is to analyze how the age factor works in Dana Vespoli’s porn and how our perception of what is obscene may change.